Effects of short-term simulated acid rain and nitrogen deposition on soil nutrients and enzyme activities in Cunninghamia lanceolata plantation - Ding, Yong; Sun, Lianhao; Li, Chong; Chen, Meiling; Zhou, Yuexiang; Meng, Miaojing; Li, Zhenghao; Zhang, Jinchi; Liu, Xin (Frontiers in Ecology and Evolution, 2024)
Acid rain and nitrogen deposition are emerging as global scale environmental issues due to increasing industrial emissions and agricultural pollutants, which seriously impac t the sustainable development of global ecosystems. However, the specific effects both acid rain and nitrogen deposition interactions on forest soil ecosystems, particularly as relates to the soil nutrient content and enzyme activities, remain unclear. Therefore, we established a simulated sample plot of acid rain (SR, NR) and nitrogen deposition (N) and their interactions (SRN, NRN) in a subtropical Cunninghamia lanceolata plantation in the Yangtze River Delta region of China to investigate the impacts of these factors via correlation analysis and structural equation model (SEM). The results showed that acid rain had a stronger effect on soil pH than nitrogen deposition in C. lanceolata plantation, while the simultaneous addition of acid rain and nitrogen deposition exacerbated soil acidification. Soil available potassium, ammonium nitrogen and nitrate nitrogen in C. lanceolata plantation responded more obviously to acid rain and nitrogen deposition, in which acid rain, nitrogen deposition and their interactions significantly reduced soil available potassium content, while acid rain and nitrogen deposition interactions significantly increased soil ammonium nitrogen and nitrate nitrogen content. Nitric acid rain, nitrogen deposition and their interactions significantly increased soil NAGase activity, but significantly decreased soil urease activity; the single-factor treatment of acid rain and nitrogen deposition significantly increased soil arylsulfatase activity, while the interaction of acid rain and nitrogen deposition significantly decreased soil arylsulfatase activity; in general, the interaction of acid rain and nitrogen deposition had a stronger effect on the soil ecosystem of the C. lanceolata plantation than that of single acid rain or nitrogen deposition, of which nitrogen deposition exacerbated the effects of acid rain on the soil ecosystem of C. lanceolata plantation mainly by changing the soil pH and the content of effective nutrients.